Combined Associations of Lead and Arsenic Species with Liver Dysfunction and Hepatic Fibrosis Among Young Adults in Taiwan - Kai-Wei Liao; Chih-Wen Wang; Wei-Lun Hung; Ya-Ling Chen; Yee-How Say; Yang-Ching Chen; Wei-Shan Chin (Exposure and Health, 2026)

Demographic, anthropometric and genetic (salt taste receptors SCNN1B and TRPV1) determinants of salt taste intensity, pleasantness, and sodium intake: Evidence from young adults in Malaysia - Muhamad Adam Razak Hamzah; Janice Xin Yi Lim; Victoria Olubunmi Olarewaju; Joshica Kaur Gill Gurcharan Singh; Geetha Letchumanan; Jack Bee Chook; Yook Chin Chia; Yee-How Say (Food Quality and Preference, 2026)

Genetic and physiological influences on sweet taste preference among young adults in Malaysia: Associations with TAS1R2/TAS1R3 variants, body composition, and food liking and intake frequency - Yee-How Say; Kah Tao Siew; Geetha Letchumanan; Victoria Olubunmi Olarewaju; Hazel Zi Qi Tham; Jue-Sheng Ong; Liang-Dar Hwang (Food Quality and Preference, 2025)

Sodium levels of canteen foods from a Malaysian higher education institution: Findings from a 7-month salt reduction interventional study - Yee-How Say; Victoria Olubunmi Olarewaju; Wen Xuan Chia; Kelvin Gunawan; Kai Hui Lee; Jia Yi Ng; Jia Ying Yeoh; Felicia Fei Lei Chung; Yook Chin Chia (Food and Humanity, 2025)

Health risk assessment of heavy metals with nephrotoxic effects from vegetables and fruits: Taiwan Food-Related Environmental Surveillance of Hazards (T-FRESH) - Kai-Wei Liao; Man-Ping Luo; Mei-Lien Chen; Yue-Hwa Chen; Yee-How Say; Wei-Shan Chin (Food and Chemical Toxicology, 2025)

Association Between Urinary Paraben Concentrations and Early Renal Impairment in Young Adults in Taiwan - Wei-Shan Chin; Yung-Ning Chuang; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Ho-Ching Kao; Man-Ping Luo; Chia-Huang Chang; Kai-Wei Liao (Exposure and Health, 2025)

The influence of exposure to inorganic arsenic and other arsenic species on early renal impairment among young adults in Taiwan - Wei-Shan Chin; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Yun-Peng Lo; Kai-Wei Liao (Environmental Pollution, 2024)

The occurrence and probabilistic risk of exposure to parabens from bottled and hand-shaken teas in the general adult population of Taiwan - Wei-Shan Chin; Chia-Huang Chang; Yee-How Say; Yung-Ning Chuang; Jui-Ning Wang; Ho-Ching Kao; Kai-Wei Liao (Environmental Science and Pollution Research, 2023)

Sensitization to Airborne Fungal Allergens Associates with Asthma and Allergic Rhinitis Presentation and Severity in the Singaporean/Malaysian Population - Yang Yie Sio; Sze Lei Pang; Yee-How Say; Keng Foo Teh; Yi Ru Wong; Smyrna Moti Rawanan Shah; Kavita Reginald; Fook Tim Chew (Mycopathologia, 2021)
Fungal spores and conidia are the major components of total airspora in the tropical Asia environment, and their sensitization patterns are often associated with allergic diseases such as asthma, allergic rhinitis (AR), and atopic dermatitis. Hence, we recruited a cross-sectional cohort of 9223 Singapore/Malaysia Chinese adults and assessed their sensitization against Curvularia lunata allergen using the skin prick test approach. A subset of this cohort ( n = 254) was also screened for specific Immunoglobulin E (sIgE) titers against a panel of 11 fungal allergens. We found significant association of Curvularia lunata sensitization with the risk of asthma (OR = 1.66, 95% CI: 1.17–2.33 ; p = 0.00391) and AR (OR = 1.69, 95% CI: 1.18–2.41; p = 0.00396). Among asthmatic patients ( n = 1680), Curvularia lunata sensitization also increased frequencies of wheezing symptoms (OR = 1.81, 95% CI: 1.05–2.96; p = 0.0239), general practitioner/specialist visits (OR = 2.37, 95% CI: 1.13–4.61; p = 0.0157), and other asthma-related exacerbation events (OR = 2.14, 95% CI: 1.04–4.10; p = 0.0289). In our serum cohort, sensitization to Aspergillus spp. was the most common fungal sensitization, with 23.6% ( n = 60) had a class 3 and above sensitization (positive sensitization; sIgE titers of > 3.5 kU/L) against this allergen. Increasing sIgE titer against Aspergillus spp. was also correlated with increased AR risk and AR-related symptoms. In conclusion, our findings emphasize an important role of fungal sensitization in the manifestations of asthma and AR in the Southeast Asian Chinese population.

A new chromanone acid from the stem bark of Calophyllum teysmannii - Chan Kiang Lim; Hemaroopini Subramaniam; Yee How Say; Vivien Yi Mian Jong; Hamid Khaledi; Chin Fei Chee (Natural Product Research, 2015)

Uncoupling protein 2 gene (UCP2) 45-bp I/D polymorphism is associated with adiposity among Malaysian women - Yee-How Say; Zi-Lian Ban; Yogambigai Arumugam; Trishal Kaur; Mee-Lay Tan; Phee-Phee Chia; Sook-Ha Fan (Journal of Biosciences, 2014)